When 'knowing what' is not enough: Role of organised simulations for developing effective practice. Issue 1 (January 2018) - Lee-Kelley, Liz
Abstract: A decade on from the Rethinking Project Management (PM) network, concerns about the relevance gap continue with a number of multinationals looking explicitly to alternative strategies and forms of PM staff development. The literature is light on how project simulations can help the development of experienced managers as reflective experts. Few have examined the link between intended learning outcomes and real-time performance. Posing the question of "how easily is knowledge developed in the classroom transformed into effective practice?" the paper presents a chronological account of a 3-day simulated project by 25 experienced managers. Despite their prior experience and learning from shared problem-solving and structured reflections, participants struggled to deliver their projects as planned. Analysis referencing the knowledge epistemology and ambidexterity literatures yielded a number of design improvement opportunities and the insight that closing the knowing-doing gap requires courses to incorporate the 'soft' perceptual and attitudinal aspects underlying why people fail to convert their learning into effective practice. Highlights: A case study of a 3-day simulated project Examining extent of classroom learning and knowledge transformation Difficult transition from experienced practitioners into reflective experts Contributing to the literature on the tacit aspects of staff development